DINAMIKA PERUBAHAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN MENGENAI BATAS USIA MINIMAL PERKAWINAN - Yuliani Catur Rini (Prodi Ilmu Hukum Universitas Nahdlatul Ulama Indonesia, 2022)
The decision of the Constitutional Court Number 22/PUU-XV/2017 has an impact on the fulfillment of the basic rights and constitutional rights of citizens, especially in terms of marriage. The logical consequence of the Constitutional Court's decision is that there is a change in the norms of Law Number 1 of 1974 concerning Marriage, which reaches the age limit for marriage. Article 7 of Law no. 1 of 1974 stipulates that the minimum age for marriage for men is 19 years and for women 16 years. The regulation was amended through Law no. 16 of 2019 which stipulates the minimum age for marriage for men and women who will marry is at least 19 years old. Changes in the minimum age for marriage have an impact on dispensation for marriage. The existence of a